2014
DOI: 10.1186/1747-597x-9-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing key characteristics of young adult crack users in and out-of-treatment in Rio de Janeiro, Brazil

Abstract: BackgroundCrack use is prevalent among street drug users in Brazilian cities, yet despite recent help system reforms and investments, treatment utilization is low. Other studies have identified a variety of – often inconsistent – factors associated with treatment status among crack or other drug users. This study compared socio-economic, drug use, health and service use characteristics between samples of young adult crack users in- and out-of-treatment in Rio de Janeiro, Brazil.FindingsStreet-involved crack us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
12

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
(34 reference statements)
1
14
0
12
Order By: Relevance
“…Authors of one study conducted in the city of Rio de Janeiro drew attention to low numbers of dependent individuals in treatment, in relation to the great demand for treatment and the urgency of the need for increased access to treatment centers. 41 The present study resembles the previous study 29 and another recent study, 16 both of which were conducted at the HPSP. All three of these studies found characteristics in common in the profiles of crack-dependent inpatients in treatment -young adult polydrug users with low incomes who have made previous attempts to stop and who exhibit high frequency drug abuse.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Authors of one study conducted in the city of Rio de Janeiro drew attention to low numbers of dependent individuals in treatment, in relation to the great demand for treatment and the urgency of the need for increased access to treatment centers. 41 The present study resembles the previous study 29 and another recent study, 16 both of which were conducted at the HPSP. All three of these studies found characteristics in common in the profiles of crack-dependent inpatients in treatment -young adult polydrug users with low incomes who have made previous attempts to stop and who exhibit high frequency drug abuse.…”
supporting
confidence: 62%
“…One of the differences identified in that study was that the group in treatment had higher socioeconomic levels and heavier usage, while not being in treatment was associated with more housing problems, lighter consumption and being a novice user. 41 There are low numbers of crackdependent individuals in treatment, in contrast to the great demand, revealing difficulty in providing access to treatment centers. 41 The present study was able to demonstrate a heavy pattern of consumption, with negative characteristics, such as a large proportion of polydrug users and escalation from licit to illicit substances, in accordance with the hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was constructed by the researchers and included variables derived from instruments previously validated in vulnerable populations (10,11,24,26,27,30,(32)(33)(34)(35)(36)(37)(38)(39) and other potential factors associated with HIV testing. The interviews were conducted by members of the study team who were professional experts in mental health and had been previously trained.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2013;CRUZ et al, 2014). Considerando-se as condições clínicas apresentadas por esses usuários, estudos têm reportado altas taxas de contágio por agentes de doenças sexualmente transmissíveis, incluindo o risco aumentado para o contágio pelo vírus HIV, principalmente entre as mulheres OLIVEIRA, 2011;ATKINSON et al, 2010;KOPETZ et al, 2013).…”
Section: ) No Brasil Dados Indicam Que O áLcool E O Tabaco São unclassified